JENIS LEBAH DAN PERANANNYA DALAM MENINGKATKAN PRODUKSI BIJI TANAMAN TIMUN (Cucumis sativus L.) DI DESA WUASA KECAMATAN LORE UTARA KABUPATEN POSO - Anie Febriani Hanyala; Sahabuddin Sahabuddin; Ramadhanil Pitopang (Biocelebes, 2016)
The research about " Bee species and ther Role in Improving Crop Seed production of Cucumber (Cucumis sativus L.) in Wuasa village of Poso Lore Utara" was carried out from July to October of 2011 the aims  of this research is to identify species of bees and their role in increasing the production of cucumber seeds. The method used is a survey method. The results showed that there were six species of bees that come to visit flowers of cucumber plants in different time. that is consisting of Amegilla, Apis cerana, Ceratinidae, Nomia, Lasiogllosum and Xylocopa. Duration visit of bee affect the amount of cucumber seed production. The dominance of the cucumber plant flower visiting bees were Apis Cerana, Ceratinidea and Nomia. The lughes seed production was most those visit by Ceratinidea than followed by Apis cerana and Nomia.   Key word :  Bee, Cucumis sativus L, Wuasa, Lore Utara Poso